When a Surrogate Knows What to Do, but Can’t Do It - Grado, Victor; Pontarelli, Maureen; Doherty, Ian; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
A surrogate or substitute decision-maker is tasked with making medical choices that the patient would make for themselves. However, most of the time the surrogate decision-maker is also emotionally involved with the patient, which makes the execution of these choices very difficult. This case study looks at a wife’s struggle to honour her husband’s wishes, because she did not want to lose him.